STRATEGIC MANAGEMENT OF EXTRACURRICULAR PROGRAMS TO ENHANCE ELEMENTARY SCHOOL QUALITY THROUGH CHARACTER DEVELOPMENT: A CASE STUDY OF SDN JOGLO 10 PAGI AND SDN SEMANAN 14 PETANG, WEST JAKARTA - Rosmawati, Rosmawati; Hidayat, Hidayat (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
Extracurricular activities play a strategic role in developing student potential and character, yet their management in elementary schools is often not based on comprehensive strategic management. Using Wheelen & Hunger’s framework, this study analyzed the management of extracurricular programs in morning and afternoon elementary schools. A qualitative case study approach was employed, involving principals, extracurricular teachers, and students through interviews, observations, and documentation. The findings indicate that strategic management was implemented through five stages: environmental analysis, strategy formulation, implementation, evaluation, and follow-up. However, each stage was conducted in a relatively simple manner, including limited needs analysis, schedule-oriented strategy formulation, and follow-up that lacked continuity. Comparison between morning and afternoon schools revealed distinct managerial dynamics: students in morning schools were generally more prepared to engage in extracurricular activities, while afternoon school students often experienced physical fatigue, limited time, and decreased motivation, resulting in less effective program management. The study highlights the need for more systematic needs analysis, participatory strategy formulation, collaborative implementation, and evaluation and follow-up based on character development outcomes to ensure extracurricular activities are meaningful and sustainable.